2019
DOI: 10.7567/1347-4065/aafed1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment and in situ high-temperature X-ray diffraction study on the formation of ferroelectric epitaxial Y-doped HfO2 film

Abstract: The process of forming the ferroelectric orthorhombic phase was investigated for epitaxial 7% Y-doped (YHO7) films using in situ high-temperature X-ray diffraction. Epitaxial YHO7 films were grown on (111) ITO-coated (111)YSZ substrates by pulsed laser deposition at room temperature and a subsequent heat treatment process. Films deposited at room temperature were crystallized as paraelectric monoclinic phase. The monoclinic phase partially changes to tetragonal phase above 600 °C and perfectly transformed arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
4
39
0
2
Order By: Relevance
“…[28,29] The details of the phase assignments can also be found in previous studies. [30,31] No spots are shown in Figure 1b, indicating that the 1100 C-treated film consists of the tetragonal phase because the existence of the other phase should lead to the appearance of the peak. On the other hand, two spots are shown in Figure 1a, which suggests the existence of monoclinic films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,29] The details of the phase assignments can also be found in previous studies. [30,31] No spots are shown in Figure 1b, indicating that the 1100 C-treated film consists of the tetragonal phase because the existence of the other phase should lead to the appearance of the peak. On the other hand, two spots are shown in Figure 1a, which suggests the existence of monoclinic films.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results on the heat‐treatment temperature dependence of the constituent phases and electric properties in the Y‐doped HfO 2 films show that the orthorhombic phase can be obtained via a higher‐temperature annealing. [ 30 ] In situ XRD measurements indicate the importance of the phase transition from the as‐deposited monoclinic phase to the tetragonal phase during the heat treatment and the transformation of the tetragonal phase to the orthorhombic phase upon cooling. Generally, the phase transition from the monoclinic phase to the tetragonal phase is a first‐order phase transition with large thermal hysteresis in fluorite oxides, such as ZrO 2 and HfO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This kinetic argument is supported by recent experimental work on the effect of heat treatment on the formation of ferroelectric epitaxial (111)-oriented 7% Y-doped HfO 2 (YHO7) thin films. 57 In this work, the as-deposited YHO7 films were heat-treated by a rapid thermal furnace at various temperatures. It was found that the as-deposited and lower temperature treatment resulted in M phase whereas a higher temperature treatment leads to more O/T phases.…”
Section: Effects Of Crystal Orientationsmentioning
confidence: 99%
“…5 Epitaxial films are being investigated now very actively. Several conducting or semiconducting substrates or templates, including Si wafers, 6 TiN, 7 GaN, 8 and indium tin oxide, 9 have been used to deposit epitaxial films of ferroelectric doped HfO 2 . In contrast, epitaxy of hafnia on perovskite-type oxide electrodes has only been reported on Nb-doped SrTiO 3 (Nb:STO) 10 and La 0.67 Sr 0.33 MnO 3 (LSMO).…”
Section: Introductionmentioning
confidence: 99%